A comprehensive analysis of Vehicle to Grid (V2G) systems and scholarly literature on the application of such - TEKİNER MOĞULKOÇ, HATİCE (ELSEVIER, 2021)
Without any doubt, the environmental issues are the top worries between all the nations in the current century. According to the recent studies, the researchers have shown that the transportation fleet is one of the biggest sources of emission. The penetrating the renewable energy sources (RESs) and electric vehicles (EVs) are the green solutions to decrease the current environmental issues. Due to intermittent nature of RESs and high investment costs of developing EVs' infrastructure, tendency for using them is under the predicted estimations. In this paper, by analyzing a precise and comprehensive literature review, we consider all aspects of implementing the EVs especially their supporting roles for the grid in vehicle to grid system (V2G). Moreover, we study the integration of the electrified fleet with RESs in smart grid and evaluate their possible impacts on the power network. In addition, we count the advantages and disadvantages of implementing the V2G system on the power network. The main purpose of this paper is analyzing the influences of the V2G system on the power grid in four main subjects and classifying them based on their proposed methodology for the future studies. However there are some review papers related to this topic, this field of study suffers a lack of clear direction for future studies and researchers and also a comprehensive analysis about the V2G-related articles is still missing. Finally, an analysis and survey of the last two decades of scholarly literature and projects in this field of study from 2004 to March 2019 is presented. The results show that a limited number of articles have conducted to investigate the social aspects of implementation of V2G system. In addition, however, there are many researches about integration of the V2G system with RESs and smart grid; a few of them use the real data for estimating the availability of RESs in each hour of day.
Keywords: IN ELECTRIC VEHICLES; RENEWABLE ENERGY-SOURCES; DISTRIBUTION NETWORKS; FREQUENCY REGULATION; SMART GRIDS; IEC 61850; OPTIMIZATION; MANAGEMENT; BATTERY; STORAGE